The role of ischemic preconditioning at the gracilis muscle of rats in the early phase of reperfusion injury - Webster,Ronaldo Scholze (2006)
PURPOSE: Verify the role of ischemic preconditioning (IPC) in ischemia and reperfusion injury on gracilis muscle of rats. METHODS: Wistar rats (n=30) were distributed in three groups, I/R and IPC groups were subdivided concerning ischemia time. A near-amputation model of the posterior limb was produced by a hip joint level incision, preserving the vascular bundle and the femur bone and ischemia was induced for 2h and 4h, G-I 2h/R (n=6) and G-I 4h/R (n=6), followed by 1h of vascular reperfusion. The preconditioned groups, G-PCI 2h (n=6) and G-PCI 4h (n=6), were preceded by 3 cycles of 5min of ischemia followed by 5min of vascular reperfusion before sustained ischemia. In the Control Group, C-G (n=6) animals were subjected to regional approach. The analysis was done with Light Microscopy (LM). RESULTS: The levels of fibril fragmentation were progressive in the G-I 2h/R (67% of muscle preservation) and in the G-I4 h/R (0% of muscle preservation). However in the group of the precondition the lesion degree being in level similar to the group controls in the G-I 2h/R (100% of muscle preservation) while at G-I 4h/r occur less protection (67% of muscle preservation). The degree of tissue inflammatory reaction was worst at G-I 4h/R (0% without inflammation signals) than at G-I 2h/R (50% without inflammation signals); while in the precondition group G-IPC-2h (83% without inflammation signals) was better than the G-IPC-4h (67% without inflammation signals). The vascular stasis was absent only in 17% of the G-I 4h/R and in 33% of the G-I 2h/R. In precondition group, however, the vascular stasis was absent in 33% at G-IPC 2h and absent in 50% at G-IPC 4h. CONCLUSION: The IPC showed, in an earlier phase, a benefic role at I/R derived injury on gracilis muscle of rats, as proven for the largest preservation of the fibers muscular, smaller inflammatory reaction and smaller vascular stasis.